MODERN ADHESIVE SYSTEMS. COMPARATIVE STUDY ON ADHESION IN DENTAL TISSUES - Bogdan Mihai Gălbinaşu; Teodor Alexandru Păunescu; Mihai Ghiţă; Ion Pătraşcu (Amaltea Medical Publishing House, 2018)
Aim. The aim of this study is to evaluate the interface between resin and hard dental tissues obtained by using two adhesive systems. Material and method. Ten extracted human molars were bonded using a total etch adhesive (Adper Single Bond 2, 3M ESPE) and a self-etching agent (Futurabond U DC, VOCO), after artificially preparing MOD cavities on them. The composite build ups were constructed using Filltek Z550 nanohybrid composite from 3M ESPE. Teeth were embedded in epoxy resin, using special vacuum equipment, then metallographic grinded to a certain point of interest and polished. The samples were analyzed using a Carl Zeiss Optical Microscope (Axio Imager A1M) and the image acquisition was made using a dedicated microscope camera (Canon Powershot A640) and dedicated software (Axio Vision). Results. Resin-enamel bonds were uniform over the entire surface on both adhesive systems whereas resin-dentin bonds resulted using the total etch system are of inferior quality (there are micro spaces between dentin and resin that range from 6,18μm to 24,12μm) than the ones resulted using the self-etch adhesive, in which case the bonds were uniform and well adapted with no signs of micro spaces. Conclusions. Resin-dentin bonds resulted using a total etch adhesive may reduce the quality of the restoration, thus being susceptible to marginal infiltration and debonding over time.